Assessment of Ground-Based and Aerial Cloud Seeding Using Trace Chemistry. (19th February 2018) - Fisher, James M.; Lytle, Marion L.; Kunkel, Melvin L.; Blestrud, Derek R.; Dawson, Nicholas W.; Parkinson, Shaun K.; Edwards, Ross; Benner, Shawn G.
Abstract : Targeting seedable clouds with silver iodide in complex terrain adds considerable uncertainty in weather modification studies. This study explores the geographic and temporal distribution of silver iodide associated with an active cloud seeding program in central Idaho snowpack using trace chemistry. Over 4, 000 snow samples were analyzed for the presence of a cloud seeding silver iodide (AgI) signature over two winter seasons. The results indicate the following. ( 1 ) At sites within 70 km of AgI sources, silver enrichments were detected at 88% of cases involving seeding efforts from ground generators, but none from aircraft seeded cases. ( 2 ) Real-time snow collection methods were replicable within 0.41 ppt and confirmed seeding signatures for the entire duration of a seeded storm (n = 3 ). ( 3 ) Sites sampled beyond 70 km of AgI sources (n = 13 ) lacked detectable seeding signatures in snow. The results of this study demonstrate some of the strengths and limitations of chemical tracers to evaluate cloud seeding operations and provide observational data that can inform numerical simulations of these processes. The results also indicate that this chemical approach can be used to help constrain the spatiotemporal distribution of silver from cloud seeding efforts.